WHERE THERE IS A VOICE, THERE IS A SPEAKER! (PALIMPSEST / ПАЛИМПСЕСТ, 2025)
The starting point of the research is the thesis of the interpretive potential of the historical novel about history and its historiographical verifications. The theoretical framework of the study is based on Linda Hutcheon's, Brian McHale's, and Elizabeth Wesseling's conceptions of the historical novel, which will be applied interpretatively to the novel Accused: Viera Gran by Polish author Agata Tuszynska. The interpretive focus is on the narrative procedures that articulate Tuszynska's novel's (re)interpretative relations to history and (meta)interpretative relations to existing textualizations of history, as well as their epistemological and (post)memorial implications.
Keywords: revisionist historical novel; interpretation; history; postmemory.